Divorcing Marriage from Sex: Radically Rethinking the Role of Sex in Marriage Law in the United States - Sally Goldfarb (Oñati Socio-Legal Series)
In 2015, the U.S. Supreme Court required all states to permit same-sex couples to marry. Many people assume that marriage equality for gay, lesbian, bisexual and transgender people has been achieved simply by eliminating the requirement that two individuals entering a marriage must be of different sexes. However, family law in the United States has traditionally required not only that married people are of different sexes, but also that they perform heterosexual intercourse. This focus on heterosexual performance threatens to undermine the legal marriages of gay, lesbian, bisexual and transgender people. It also threatens the dignity, privacy, and legal validity of some heterosexual couples’ marriages. Contrary to current practice, the law should make no assumptions about the existence or type of sexual behavior between spouses that is necessary to create and sustain a marriage.